Penerapan Perilaku Sehat penjamah Makanan Pada Masa Pandemi Di Objek Wisata Aji Bata Kabupaten Toba - Enny Hasriani; Muhammad Zulfan (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
Application is an act of putting into practice a theory, method, and other things to achieve a certain goal and for an interest desired by a group or class of healthy behavior, is a person's response to stimuli related to illness and disease, the health care system, food, As well as the Environment. Human Responses Or Reactions, Both Passive (Knowledge, Perception, And Attitudes) Or Active (Concrete Actions Or Practice). Food Handlers Are People Who Are Directly In Contact With Food And Equipment, From The Stages Of Preparation, Cleaning, Processing, Transportation To Serving. A restaurant is a place or building that is commercially organized, which provides good service to all consumers, both in the form of food and drinks. This type of research is descriptive analysis, namely the research method by observing the problems that exist at the moment and then analyzing the data. The subjects of this research are food handlers who work in restaurants and restaurants around the Ajibata tourist attraction, totaling 50 Responde. Data is collected by providing questionnaires in the form of questionnaires, then the questionnaires are collected as data, then the data is analyzed. The results of the analysis show that overall the food handlers who work in restaurants/eateries around the Ajibata Tourism Area during this pandemic have implemented healthy behavior when working in the work environment.